Factores asociados a pensamientos suicidas en adolescentes de la Unidad Educativa Comunitaria Intercultural Bilingüe ABC de Tenta - Puchaicela Lozano, Félix Aníbal (2023)
Suicidal thoughts are part of a process framed in suicidal behavior that can progress to its execution, it is considered a public health problem worldwide and in Ecuador, where the incidence has been increasing in recent years. There are psychosocial risk factors that are associated with its high frequency, among these, self-esteem, family problems and psychoactive substance use tend to be the most prevalent. Due to the relevance of the topic, this descriptive, quantitative, observational, cross-sectional correlational prospective cohort study aimed to determine the factors associated with suicidal thoughts in adolescents of ABC Intercultural Bilingual Community Education Unit, in Tenta parish, with a total of 85 high school students. For this purpose, the Positive and Negative Suicidal Ideation Test PANSI, the APGAR Family Dysfunction Test, the Rosemberg Self-Esteem Test, and the ASSIST Drug and Alcohol Consumption Test were used. It was found that 11.76% (n=10) of the entire population presented a moderate and high risk for suicidal thinking. Next to the psychosocial factors, it was observed that 25.88% (n=22) corresponded to mild family dysfunction and 3.53% (n=3) to severe family dysfunction; likewise, 48.24% (n=41) presented low self-esteem and finally 45.88% (n=39); 22.35% (n=19) consumed alcoholic beverages and tobacco respectively. The study concludes that the adolescent population of the Educational Unit presented a notorious prevalence of suicidal thinking accompanied by psychosocial factors that determined the existence of suicidal ideation